2015
DOI: 10.11113/jt.v75.5275
|View full text |Cite
|
Sign up to set email alerts
|

The Principle of Depth for Underground Land Development: A Review

Abstract: In this era, the developments are not taking place at the surface land, but also going downward by utilizing the underground land. The importance for developing underground land cannot be denied since worldwide has the good example of underground land development especially in the infrastructure development. In developing underground land, the depth is one of the considerations to determine how deep the construction can go underground. However, in relation with the ownership and restrictions in developing unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Municipalities worldwide host complex infrastructure networks that exist partially or entirely belowground. Components of this infrastructure facilitate transportation, provide structural support for buildings, distribute drinking water, enable sanitation, and manage stormwater (Zaini et al 2015). Shallowing of coastal groundwater is known to cause an array of impacts on the various network components that perform these crucial functions (Abdelhafez et al 2022, Knott et al 2017, Luo et al 2015, Miranda et al 2019, Osman et al 2017) (Figure 3).…”
Section: Impacts Of Sea-level-rise-influenced Coastal Groundwatermentioning
confidence: 99%
“…Municipalities worldwide host complex infrastructure networks that exist partially or entirely belowground. Components of this infrastructure facilitate transportation, provide structural support for buildings, distribute drinking water, enable sanitation, and manage stormwater (Zaini et al 2015). Shallowing of coastal groundwater is known to cause an array of impacts on the various network components that perform these crucial functions (Abdelhafez et al 2022, Knott et al 2017, Luo et al 2015, Miranda et al 2019, Osman et al 2017) (Figure 3).…”
Section: Impacts Of Sea-level-rise-influenced Coastal Groundwatermentioning
confidence: 99%
“…In some investigations, legal issues of underground space and the ownership of this space in different countries and jurisdictions have been studied [13,18,30,42,43,[45][46][47][48][49][50][51]. Most of these studies concluded that underground property rights are not adequately stabilising public and private interests in the underground.…”
Section: Current Challenges In Ula 31 Legal Challengesmentioning
confidence: 99%
“…Specific minimum depth of disposal of underground land is not very common in national legislation. For example, in Malaysia, the minimum depth of underground space disposal ranges from 6 to 15 m, depending on surface parcel land use (Zaini et al, 2013); in the state of Victoria in Australia, alienation of Crown land is allowed only up to the depth defined by the Governor in Council, while in Finland, underground land can be freely utilised up to a depth of 6 m (Vähäaho, 2014). The difference in the Finnish case is that the surface parcel owner owns the underground of his parcel, despite the depth limitation, but does not have the right to use it for construction purposes deeper than 6 m without a permit (Vähäaho, 2014).…”
Section: Introductionmentioning
confidence: 99%